Study of The Experimentally Zinc Deficiency in Iraqi Local Breed Goats - Al-Zubaedi, Mahmood Raad; Mahmood, Alaa K.; Al-Khafaji, Nazar Jabbar (The Iraqi Journal of Veterinary Medicine, 2019)
The current study was conducted to study experimentaly induced zinc deficiency and its consequnces hematology in Iraqi goats. A twenty five goats, 5-6 months old were involved in this study. The study extended from November 2018 continued for 10 weeks in the farm of College of Veterinary Medicine, University of Diyala. The animals were fed a high calcium content ration (400-500 gm/head/day) in addition to hay and water with ad libitum during the study. The main clinical signs were retardation in hair growth, especially of legs and head, swollen joint, poor growth, rough hair coat, loss of hair on head, limbs, and scrotum, cracking of the hooves. The skin rough, thickened, cracked, alopecia, crusting, and hyperkeratosis also paleness of the mucous membranes of the eye, loss of appetite, itching, and emaciation. Body weight, heart rates, and body temperature were not significantly changed, respiratory rates significantly decreased in 3rd and 6th weeks in comparison with 1st week. The results of total red blood cells counts revealed significantly decreased in the 2nd week compared with 1st week, then increased in the 4th, 6th and 8th weeks in comparison with1st week. Hemoglobin concentration significantly increased at the 2nd, 4th and 6th weeks in comparison with the 1st week. Packed cell volume increased at the 2nd, 4th, 6th and 8th weeks compared with 1st week. Serum zinc was significantly decreased from the 2nd week till the end of the experiment.Significant decrease in lymphocytes was detected at the 4th week compered with 1, 2, 6 and 8 weeks. Eosinophil was also significantly decreased in the 2nd and 6th weeks compared with 1st week, and increased 4th week and 8week compared with 2nd ,6th respectively.It is concluded from this study that zinc deficiency clearly affects the overall health status and may eventually lead to economic losses in local goats.